Comparative Analysis of Bladder Volume Consistency Using Portable Ultrasound Scanners and Biofeedback in Radiotherapy for Pelvic Tumors - Haitao Wang B.Sc.; Lu Zeng M.S.; Quan Zhong M.S.; Zhonghua Deng B.Sc.; Renming Zhong PhD (Technology in Cancer Research & Treatment)
Purpose To evaluate the accuracy of two bladder scanners (BS) in measuring bladder volume (BV) during radiotherapy (RT), and explore the influence of two bladder filling methods and patients’ subjective urinary sensation on the consistency of BV. Methods Forty-two patients with pelvic tumors were divided into two groups: Group A (20 patients) and Group B (22 patients). Before the planning CT and each treatment session, all patients drank 500 mL of water after emptying their bladder and rectum. Group A waited for patients to provide feedback on urination, while Group B waited for 1 h. Subsequently, three consecutive measurements using two BSs were performed. The average volumes measured by the BS Padscan HD5 and Padscan HDW1 were recorded as BSHD5-v and BSHDW1-v, respectively. The differences between BSHD5-v, BSHDW1-v, and the BV obtained from planning CT (CT-v) or cone beam CT (CBCT) (CBCT-v) were assessed. The consistency between CBCT-v and CT-v in two patient groups was calculated. Urinary sensation score BV (V SC ) was determined by the patient's urge to urinate score and CT-v. Results The average CT-v or CBCT-v was 280 mL (range 78-710 mL, SD = 119 mL). BSHD5-v had an average of 271 mL (range 61-611 mL, SD = 115 mL), with a significant correlation with CT-v or CBCT-v (R = 0.89, p < 0.001). BSHDW1-v averaged 267 mL (range 92-634 mL, SD = 77 mL), positively correlated with CT-v or CBCT-v (R = 0.70, p < 0.001). Group A's CBCT-v proportions within ±20%, ± 30%, and ±50% of CT-v were 51.20%, 66.90%, and 91.90%, respectively, contrasting with Group B's 26.2%, 41.1%, and 67.7%. V SC exhibited a positive association with CBCT-v (R = 0.59, p < 0.001). Conclusions Consistent and reproducible bladder volume was obtained by using Padscan HD5 and Padscan HDW1. The Padscan HD5 demonstrated greater consistency and accuracy. Furthermore, the urinary feedback method has a more consistent bladder volume than the fixed-time method.